Killer kung pao - Chien, Vivien (Chien, Vivien. Noodle shop mystery, 2020)
"Lana Lee's plate is already plenty full. Running her family's Chinese restaurant in Cleveland's Asia Village is challenging on the best of days. But just when Lana thinks she might be able to catch her breath before the weekend--which she's eager to spend with her equally overworked boyfriend, Detective Adam Trudeau--Lana witnesses a car accident in the parking lot. And now she has no choice but to get involved. June Yi, of Yi's Tea and Bakery, is a serious businesswoman well-known for her heartlessness. But June meets her match when she rear-ends the Cadillac belonging to Mah Jong lover Mildred "Millie" Mao. As each woman curses--and threatens--the other, it becomes clear to Lana that trouble lies ahead. Still, who could have imagined that Millie would end up dead at the beauty salon? The evidence suggests that she was electrocuted while having a foot bath, and all eyes are on June. Can Lana find a way to solve this case before another fatality occurs in Asia Village?"--Page [4] of cover.